Towards investigative training in the business administration programme of the universidad de la Amazonia (2021-2028), Caquetá - Colombia (2022)
The objective of this article is to design a proposal to strengthen research training in the Business Administration program of the Universidad de la Amazonia, Colombia. The research is descriptive and propositional. A sample of 389 students was determined by simple random sampling. The study used correlation analysis and the elaboration of a SWOT (Weaknesses, Opportunities, Strengths, Threats) matrix. The results indicate that for 70% of the students, research is a complex process and mentally unrelated to their professional training. It concludes with: the proposal of awareness-raising activities aimed at students, the identification of course units that include applied research, the promotion of participation in research groups and hotbeds, an increase in academic credits in the curriculum as support for the degree option and the restructuring of the research lines of the program.